A functional assessment of the impact of changing grazing management of upland grassland mosaics. Issue 4 (22nd June 2020) - Pakeman, Robin J.; Fielding, Debbie A.
Abstract: Questions: How do changes in grazing impact functional traits in habitat mosaics? Which habitats are sensitive to management changes? Location: Mosaic of open upland habitats, including Agrostis–Festuca and Nardus grasslands, Carex and Molinia mires, bracken and wet heath, southern Highlands of Scotland, UK. Methods: Four grazing treatments were started in 2002: (a) Continued grazing at 0.9 ewe/ha (control); (2) High — 2.7 ewe/ha; (c) Mixed — partial substitution of sheep by cattle; and (d) None. Vegetation was sampled at 25 permanently marked locations per plot every three years. Analysis assessed how grazing affected community‐weighted means of selected traits at the whole plot level and community level. Results: Whole plot level changes in trait means were negligible apart from a small reduction in height in the High and Mixed treatments and a shift to earlier flowering in the High treatment. At the community level, increased grazing generally led to a reduction in canopy height and earlier flowering. Both increased and reduced grazing reduced leaf dry matter content (LDMC) in the most preferred community, Agrostis–Festuca grassland, but reduced grazing increased LDMC in the least preferred community, wet heath. Cattle grazing reduced LDMC in both Agrostis–Festuca grassland and wet heath and reduced height in bracken. Conclusions: Despite significant changes in grazing there were only small changes in trait means over 15 years. The most preferred communities were less sensitive to grazing removal than expected; few species present can take advantage of reduced grazing. The least preferred communities were more sensitive to grazing removal than expected; they still contain species capable of exploiting this. The presence of more preferred communities in each plot meant increased grazing has less impact on communities of moderate and low preference. Cattle impacts were highest in the communities most sensitive to trampling, bracken and wet heath. Abstract : We analysed functional traits changes in a large, upland grazing experiment. Plot level changes in trait values were small, showing the resistance of the habitat mosaic to changing grazing management. Responses were most pronounced in the unpreferred wet heath, which still contained species capable of exploiting reduced grazing. Cattle impacts were highest in the trampling‐sensitive bracken and wet heaths.